1996
DOI: 10.1177/107755879605300405
|View full text |Cite
|
Sign up to set email alerts
|

Equalizing Physician Fees had Little Effect on Cesarean Rates

Abstract: Higher physician fees for cesarean delivery have been hypothesized to increase cesarean rates, but there are few published estimates of their effect. We studied the impact of an insurance reform that equalized fees for vaginal and cesarean delivery, a relative price shift of 21%. After adjusting for case-mix, cesarean rates were calculated from data on the 11,767 deliveries in the 12 months before and after the reform. Overall, there was a 0.7% nonsignificant drop after the reform. The drop was apparently due … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
42
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 6 publications
5
42
1
Order By: Relevance
“…In current dollars, a $1000 increase in the reimbursement for performing a cesarean section would increase cesarean delivery rates by little more than one percentage point. This finding jibes with that of the closest related study, by Keeler and Fok (1996), of a cesarean/vaginal fee equalization at one insurer. It contrasts with that of Currie and Gruber (2001), who find even larger effects than GKM using a fully national dataset but a less direct research design.…”
Section: Resultssupporting
confidence: 88%
“…In current dollars, a $1000 increase in the reimbursement for performing a cesarean section would increase cesarean delivery rates by little more than one percentage point. This finding jibes with that of the closest related study, by Keeler and Fok (1996), of a cesarean/vaginal fee equalization at one insurer. It contrasts with that of Currie and Gruber (2001), who find even larger effects than GKM using a fully national dataset but a less direct research design.…”
Section: Resultssupporting
confidence: 88%
“…These weak and/or insignificant income effects are consistent with the results from the studies in the United States that found no volume response or only a weak volume response to changes in remuneration per item of treatment [8,10,11,12]. The findings are also consistent with the results from several other studies of primary physicians in Norway [1,4,5,21].…”
Section: Discussionsupporting
confidence: 90%
“…However, they say little about how great the income effects are since they do not distinguish between the substitution and income effects of changes in remuneration per item of treatment. Other studies found no volume response,or only a weak volume response to changes in remuneration per item of treatment [8,10,11,12]. For example,Hurley et al [10] studied how physicians responded to changes in remuneration per item of treatment for 28 medical procedures during the period 1977-1988 in the Canadian Province of Ontario.They found no volume response for most of the procedures.Their results are supported by similar studies from four other provinces during the period 1977-1989 [11].…”
Section: Results From Earlier Studiesmentioning
confidence: 99%
“…Previous studies have found that cost is possibly associated the cesarean delivery [12,13]. Few studies have examined the relationship between the reimbursement system and the cesarean delivery rate [17][18][19]. Because, the average cost of a cesarean delivery is at least two times higher than that of a vaginal delivery, the healthcare provider may be required to perform additional unnecessary procedures due to cost differences [20].…”
Section: Introductionmentioning
confidence: 99%